"THE IMPACT OF ARTIFICIAL INTELLIGENCE ON THE EDUCATION PROCESS" (International conference on multidisciplinary science, 2025)
In the 21st century, the development of the educational process is significantly changing in connection with the widespread use of modern technologies, especially artificial intelligence. The use of artificial intelligence technologies in the educational process not only optimizes the teaching process by considering the individual needs of students, but also simplifies pedagogical activities and increases their effectiveness. For this reason, the integration of artificial intelligence into the education sector is increasingly becoming an important component of modern pedagogy.